Cancer Stem Cells in Intrahepatic Cholangiocarcinoma; Their Molecular Basis, and Therapeutic Implications - Tamai, Keiichi; Fujimori, Haruna; Mochizuki, Mai; Satoh, Kennichi (Frontiers in Physiology, 2022)
Cancer tissue consists of heterogenous cell types, and cancer stem cells (CSCs) are a subpopulation of the tissue which possess therapy resistance, tumor reconstruction capability, and are responsible for metastasis. Intrahepatic cholangiocarcinoma (iCCA) is one of the most common type of liver cancer that is highly aggressive with poor prognosis. Since no target therapy is efficient in improving patient outcomes, new therapeutic approaches need to be developed. CSC is thought to be a promising therapeutic target because of its resistance to therapy. Accumulating evidences suggests that there are many factors (surface marker, stemness-related genes, etc.) and mechanisms (epithelial-mesenchymal transition, mitochondria activity, etc.) which are linked to CSC-like phenotypes. Nevertheless, limited studies are reported about the application of therapy using these mechanisms, suggesting that more precise understandings are still needed. In this review, we overview the molecular mechanisms which modulate CSC-like phenotypes, and discuss the future perspective for targeting CSC in iCCA.